2010
DOI: 10.1088/0957-0233/21/7/075103
|View full text |Cite
|
Sign up to set email alerts
|

Waveguide effects on quasispherical microwave cavity resonators

Abstract: The perturbing effect of a waveguide on the boundary of a quasispherical cavity resonator is investigated both theoretically and experimentally. Expressions for the frequency perturbation to the triply degenerate TM1mn and TE1mn modes are derived using cavity perturbation theory. The fields in and around the waveguide are calculated in the static limit using finite-element software. Experiments performed using quasispherical and cylindrical cavity resonators confirm the accuracy and generality of the approach.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 17 publications
1
69
0
Order By: Relevance
“…For such geometry, a theoretical calculation of the second-order corrections of microwave eigenvalues has only recently been completed [21], and found to be in outstanding agreement with the results of experiments [22].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…For such geometry, a theoretical calculation of the second-order corrections of microwave eigenvalues has only recently been completed [21], and found to be in outstanding agreement with the results of experiments [22].…”
Section: Introductionmentioning
confidence: 83%
“…In 1986, Mehl and Moldover [12] used first-order perturbation theory to prove that the mean eigenfrequency of a multiplet is independent of volume-preserving deformations, and suggested that the volume of an imperfect spherical resonator could thus be determined from its microwave spectrum. Several of our earlier papers have set the groundwork for this determination [2,3,16,20,22].…”
Section: Measurement Of the Volume Of The Resonatormentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the average radius of BCU3 has been determined from measurements of the frequencies and half-widths of nine microwave triplets, corrected to take into account three effects: (i) the microwave penetration depth using measured half-widths of the resonances, as described by Sutton et al [2], (ii) the inlet and outlet gas ducts and the two microwave antennas using the extensive study of the effects of probes and holes in a quasi-spherical resonator (QSR) performed by Underwood et al [22], and (iii) the shape of the QSR, using second-order theory [21] and our measurements of the frequency splitting of the microwave triplets. The determination of the equivalent radius and its uncertainty budget was accomplished in four steps.…”
Section: Precise Measurement Of the Volume Of The Resonatormentioning
confidence: 99%
“…We corrected these frequencies to account for shape and probe perturbations using the models and the results in Underwood et al [22]. -With loop antennas, we determined the electrical conductivity of the copper surface and established a bound on any dielectric layer on the surface, in the same experimental conditions (20 • C and flowing argon) as those specified for the previous step.…”
Section: Precise Measurement Of the Volume Of The Resonatormentioning
confidence: 99%